Mathematical communication ability of 7th grade in SAVI learning with elaborated feedback - Kurniawati, Devy; Kartono, Kartono (Unnes Journal of Mathematics Education, 2021)
Mathematical communication ability is important to communicate ideas and improve students' understanding. The purpose of this study was to examine the effectiveness of SAVI learning with elaborating feedback towards the students' achievement of mathematical communication abilities; and to describe how to students' achievement of mathematical communication abilities with elaborated feedback. The population of this study is 7th-grade students in one of the junior high schools in the city of Semarang year 2018/2019. Sampling by simple random sampling techniques and subject selection with purposive sampling technique. The results of the study showed that SAVI learning with elaborated feedback is effective in the students' achievement of mathematical communication abilities. Description of students' mathematical communication abilities, namely (a) high group subject have mastered four indicators of mathematical communication; (b) medium group subject have mastered three indicators of mathematical communication, and (c) the low group subject have mastered 2 and 3 indicators of mathematical communication.